2011
DOI: 10.2217/pme.11.39
|View full text |Cite
|
Sign up to set email alerts
|

Provision of Personalized Genomic Diagnostic Technologies for Breast and Colorectal Cancer: An Analysis of Patient Needs, Expectations and Priorities

Abstract: This study demonstrates breast and colorectal cancer patients' willingness to adopt and pay for novel genomic diagnostics, as well as identifies several salient factors associated with patient preferences for genomic diagnostics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…5 Analysis of focus groups and interviews also showed that people generally held positive views of pharmacogenomics. 10,14,[22][23][24][25][26][27] It is important to highlight that, unlike other surveys involving patients suffering from chronic medical conditions, 11,12 patients in our study were not recruited among participants of a larger pharmacogenomic project. Instead, HF and heart transplant patients were identified directly from our institution's clinics and were introduced to pharmacogenomics by an investigator right before completing the questionnaire.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 Analysis of focus groups and interviews also showed that people generally held positive views of pharmacogenomics. 10,14,[22][23][24][25][26][27] It is important to highlight that, unlike other surveys involving patients suffering from chronic medical conditions, 11,12 patients in our study were not recruited among participants of a larger pharmacogenomic project. Instead, HF and heart transplant patients were identified directly from our institution's clinics and were introduced to pharmacogenomics by an investigator right before completing the questionnaire.…”
Section: Discussionmentioning
confidence: 99%
“…Possible explanations for these intergroup differences include the fact that HF patients were older and more frequently retired and that many patients had already been denied insurance coverage due to their chronic illness. Although the group variable was not independently associated with the common fear of disclosure to unauthorized persons, 6,[10][11][12]14,[20][21][22]25,27,29,35,39,41 healthy volunteers appeared to be more worried about this possible lack of confidentiality. These observations are noteworthy, because healthy individuals such as those interviewed in our survey will most likely be the patients of tomorrow.…”
Section: Discussionmentioning
confidence: 99%
“…A total of nine studies focused on the patient perspective as it relates to PG testing (Table ) . Most studies were performed in the United States (n=6), with the remaining studies conducted by researchers based in Japan, Germany, and Australia.…”
Section: Resultsmentioning
confidence: 99%
“…Eliminates toxicities of ineffective treatment "We use it in patients who are metastatic, who the whole goal of therapy is palliative. And for them to get these many side effects with no benefit doesn't make sense" (14). Conserves resources "For us … cost is not an issue.…”
Section: Benefits Of Kras Testing Explanation/quotementioning
confidence: 99%
“…Test outcomes due to use of proper tissue specimen "I don't know if you get the most benefit if it's the primary lesion or if it's a secondary lesion. I don't know if you test if the sample hasif it's a fresh sample or if you can get a block and test it many years later" (14). Test does not predict treatment response "The only thing is that you would rather have a test that tells you which patient responds, not which one doesn't respond.…”
Section: Concerns With Kras Testing Example/quotementioning
confidence: 99%